AZIMJON HAJIYEV'S VIEWS ON LINGUISTICS (Neo Scientific Peer Reviewed Journal, 2025)
A prominent figure in linguistics, Azimjon Hojiyev, made significant contributions to the study of language and its structure. This article examines his views on various aspects of linguistics, including language acquisition, syntax, semantics, and pragmatics. By analyzing his works and scientific contributions, we aim to provide a deeper understanding of Hojiyev’s unique perspective on linguistics and its impact on the wider field.